The Influence of Slopes to the Stability of Stones in front of Seawall - Haryo Dwito Armono; Danny Indra Setyawan; Muhammad Zikra (International Journal of Offshore and Coastal Engineering (IJOCE), 2017)
Seawall is a coastal protection structure to prevent coastal erosion from wave forces. In this research, rubble-mound of stones are used as armor due to the availability of the material in coastal areas and ease of construction. A series of physical model tests with a scale of 1:25 with a variation of four wave heights (H), two wave periods (T), and three different slopes of rubble-mound in front of seawall were performed. Parameters used in the research are stability coefficient (KD),wave steepness (H/gT2), and percentage of damages (Do). The slope variations of rubble-mound were 1:1.15, 1:1.5, and 1:2. The experiments also displayed that the stone stability coefficient (KD) directly proportional with wave steepness (H/gT2). The value of KD for the seawall model with the slope angle of cot = 1.15 is 4.4, cot = 1.5 is 4.28 and cot = 2 is 3.02. From all three variations of slope, the most stable is on the slope 1:2 with the least damage impact on the model. The gentlest slope is the most stable structure.